2015
DOI: 10.3390/s150612342
|View full text |Cite
|
Sign up to set email alerts
|

A New, Effective and Low-Cost Three-Dimensional Approach for the Estimation of Upper-Limb Volume

Abstract: The aim of this research was to validate a new procedure (SkanLab) for the three-dimensional estimation of total arm volume. SkanLab is based on a single structured-light Kinect sensor (Microsoft, Redmond, WA, USA) and on Skanect (Occipital, San Francisco, CA, USA) and MeshLab (Visual Computing Lab, Pisa, Italy) software. The volume of twelve plastic cylinders was measured using geometry, as the reference, water displacement and SkanLab techniques (two raters and repetitions). The right total arm volume of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Buffa et al [11] reported that a 3D scan technique yielded volume data of an upper arm that were reliable and valid. In that study, volume error measures of an arm were between 1.4% and 2.6% -which is similar to the error observations we made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Buffa et al [11] reported that a 3D scan technique yielded volume data of an upper arm that were reliable and valid. In that study, volume error measures of an arm were between 1.4% and 2.6% -which is similar to the error observations we made.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, scans were made by having the researcher freely move the scanner around the object of interest. Buffa et al [11] constructed a device that controlled the movement of the scanner about the object. It seems that the error we observed was reasonable especially given the lack of control of movement of the scanner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the consistency of measurements taken using 3-D scanning with those taken using water displacement in this study. Although a very high correlation between the conventional method and 3-D scanning method was observed, the %LOA was -4% to 7%, compared to a %LOA of water displacement of −2.6% to 1.4% [ 22 ]. While the 3-D scanning method was less accurate than the water displacement method, the error caused by the 3-D scanning method is considered to be clinically acceptable given the advantages over water displacement.…”
Section: Discussionmentioning
confidence: 99%
“…However, CT and laser scanning require expensive equipment, intricate workflows, and trained operators, and therefore are resourceintensive [3,5,6]. Structured light scanning could be implemented through low-cost hardware and software, but its accuracy is not sufficient for skeletal anthropology applications [7,8].…”
Section: Introductionmentioning
confidence: 99%